Tracking control for nonholonomic wheeled mobile robot with wheel slip dynamics - Yu, Tian; Sidek, Shahrul Na'im; Sarkar , Nilanjan (2010)
In order to model a Wheeled Mobile Robot (WMR) system to improve its maneuverability in a real environment, wheel dynamics, which may violate no-slipping and pure wiling constraints, needs to be studied. In this paper, wheel dynamics with slip is modeled and introduced into the robot overall dynamics. Wheel slip phenomenon is captured and at the same time accommodated. Considering both lateral and longitudinal slip phenomena due to traction, a WMR system becomes an underactuated dynamic system with second order nonholonomic constraints. Position tracking control law is developed to asymptotically stabilize the system while it is converging to the desired trajectory, if the traction is not saturated. Simulation results are provided to validate the theoretical results.